Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1302/0301-620x.101b4.bjj-2018-1316.r1
|View full text |Cite
|
Sign up to set email alerts
|

Do oxidized zirconium heads decrease tribocorrosion in total hip arthroplasty?

Abstract: Aims The aim of this study was to evaluate fretting and corrosion in retrieved oxidized zirconium (OxZr; OXINIUM, Smith & Nephew, Memphis, Tennessee) femoral heads and compare the results with those from a matched cohort of cobalt-chromium (CoCr) femoral heads. Patients and Methods A total of 28 OxZr femoral heads were retrieved during revision total hip arthroplasty (THA) and matched to 28 retrieved CoCr heads according to patient demographics. The mean age at index was 56 years (46 to 83) in the OxZr gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…Conceptually, OxZr has improved wettability and scratch resistance compared with CoCr, and reduced femoral head fracture risk compared with ceramics. 3,16 In the current study, there was a non-statistically significant trend towards reduced wear rates in OxZr femoral compared to CoCr heads, when articulating with XLPE at seven and ten years' follow-up. Interestingly, several other studies have reported similar trends in wear rates between OxZr and CoCr and, similar to the current study, these differences did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Conceptually, OxZr has improved wettability and scratch resistance compared with CoCr, and reduced femoral head fracture risk compared with ceramics. 3,16 In the current study, there was a non-statistically significant trend towards reduced wear rates in OxZr femoral compared to CoCr heads, when articulating with XLPE at seven and ten years' follow-up. Interestingly, several other studies have reported similar trends in wear rates between OxZr and CoCr and, similar to the current study, these differences did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 52%
“…These consist of a zirconium and niobium alloy created by thermal diffusion, producing a 5 μm-thick zirconium-oxide ceramic layer on a metal alloy core. 16 Conceptually, OxZr combines the internal strength and durability of metals, with the increased wettability, surface hardness, and abrasive wear resistance of ceramics. 3,16 Retrieval analysis has shown that OxZr femoral heads are associated with reduced mean corrosion rates at the head-neck junction compared with CoCr femoral heads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 With concerns of tribocorrosion and longterm survival, previous studies have shown OxZr to be superior to both MoP and CoP. 9,30 As Kurtz et al 13 and Mendenhall 31 have shown, the cost differentials between CoP and MoP bearings continue to decrease with time and may soon be cost neutral. While the cost to manufacture OxZr and CoP bearings is beyond the scope of this paper, improvements continue to be made with both bearings and costs to manufacture these continue to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the OxZr heads have shown to exhibit lower amounts of fretting and corrosion compared with other bearing articulations, supporting their use in larger head sizes and potentially avoiding instability issues. 9 As the use of the OxZr bearing is limited to those stems being utilized with Smith and Nephew due to the OxZr being proprietary technology, the use of this bearing with the R3/ Polarstem has seen excellent results in the United Kingdom National Joint Registry (NJR). 10,11 As the R3/Polarstem with the OxZr has the lowest revision rate in the NJR and having a 7A rating by the Orthopaedic Data Evaluation Panel (ODEP), the use of this combination of bearing and cementless THA system has seen good results even at mid-term follow-up with a low revision rate.…”
mentioning
confidence: 99%